Tourette Syndrome: A Mini-Review - Novotny, Michal; Valis, Martin; Klimova, Blanka (Frontiers in Neurology, 2018)
The purpose of this mini-review is to provide the latest information on epidemiology, pathophysiology, diagnosis and treatment of Tourette syndrome (TS). The authors conducted a literature search of available sources describing the issue of tic disorders with special focus on TS and made a comparison and evaluation of relevant findings. The results of this mini-review indicate that TS is a complex disorder, which has a significant impact on the quality of life of both the patients and his/her family. Therefore, early and proper diagnosis and treatment are necessary in order to reduce or even eliminate both symptoms and social burden of the patient. This requires a multidisciplinary management approach in order to meet the patients’ special needs. Future research should focus on neuroimaging, new neurotransmitter targets, in functional neurosurgery, as well as the effect of non-pharmacological psychotherapies for these people.